Pengambilan Fe, Mn dan Cu oleh nepenthes sp. dalam tanih bekas Lombong Pelepah Kanan Kota Tinggi, Johor - Sahibin Abd. Rahim,; Tukimat Lihan,; Zulfahmi Ali Rahman,; Wan Mohd Razi Idris,; Azman Hashim,; Sharilnizam M. Yusof,; Liow, Hai Yin, (Universiti Kebangsaan Malaysia, 2007)
Heavy metals content of Fe, Mn and Cu in soil and Nepenthes sp. in a former iron and tin mining land at Lombong Pelepah Kanan, Kota Tinggi, Johor were determined. Heavy metal content were determined in four plant component namely roots, stems, leaves and pots. A number of 15 Nepenthes sp. plants and their corresponding substrate samples were collected for analysis. The composition of heavy metals in soil were extracted using mixture of nitric acid and perchloric acid. Heavy metals content in plants sample were extracted by wet digestion method. Heavy metal content in solution extract of soil and plant component were determined with Flame Atomic Absorption Spectrophotometer (FAAS). The BAC (Biological Absorption Coefficient) was calculated as ratio of the heavy metal concentration in plant to that of its substrate. The analyses of soil showed that the former mining area was dominated by sand and acidic. It also has a low content of organic matter and low reading of soil electrical conductivity. The soil contain higher concentration of Fe followed by Mn and Cu. Based on BAC value Nepenthes sp can be used as a bio-indicator for Fe.